Application of Load Duration Curve Method in Pollution Control in the Middle and Lower Reaches of Hanjiang River - ZHAO Chen; CHEN Yanfei; DONG Yuru; SUN Yongxi (Renmin Zhujiang)
The load duration curve method is used to study both water quality change and pollution load.This study aims to examine the effect of pollution control in the middle and lower reaches of the Hanjiang River and puts forward reasonable pollution control measures.For this purpose,the load duration curves of total phosphorus,CODMn,and ammonia nitrogen are drawn according to the hydrological data and water quality data for 2006—2020,with water pollution prevention and control and the local water quality requirements as the design water quality objectives.The relationships among water flow,water quality,and pollution load are thereby established.The results show that under the corresponding specified surface water quality,the CODMn,ammonia nitrogen,and total phosphorus indexes of the Huangzhuang section all meet the requirements,and the residual load is large,which means that no reduction measures are needed.Regarding the Xiantao section,reduction measures are also unnecessary for CODMn and ammonia nitrogen,which,nevertheless,is not the case for the high and low flow areas of total phosphorus.The reduction amounts for the two areas are 6.05 t/d and 0.09 t/d,respectively.This study provides technical support for water quality compliance management under different hydrological conditions of the river.